Use of nets treated with food grade coatings on controlling mold growth and mite infestation in dry-cured ham aging facilities. (December 2020) - Campbell, Yan; Shao, Wenjie; Dinh, Thu; To, Kezia; Rogers, William; Zhang, Xue; Phillips, Thomas; Schilling, Wes
Abstract: Dry-cured hams are frequently infested by mold and Tyrophagus putrescentiae in the aging facility during the 3 mo to 2-year aging period. Food grade coatings and these coating treated nets have been developed to control mold and mite growth on dry-cured hams to curtail the use of methyl bromide. Ham nets treated with food-grade coating of 1% propylene glycol alginate + 1% carrageenan + 40% propylene glycol were tested in a commercial research trial in 3 lots with approximately 100 hams in each lot, which also had approximately 100 control hams (untreated). Six of these hams were sent back to the research team. Three of these hams (already aged for 8 mo) were kept in a mite-infested simulated aging room for further evaluation of mold occurrence and mite population growth for another 6 mo. The other 3 hams from each lot of each treatment were tested by gas chromatography for propylene glycol residual. Mold evaluation indicated that the treatment hams reduced mold occurrence compared to the control hams, and there were no mite activities in any of these hams per inspection. In the mite-infested aging room, these coating-treated nets reduced mold and mite growth on whole hams (8–14-month-old). There was no difference in propylene glycol concentration between the control (0.072%) and net treated samples (0.053%). This concentration is 4 times less than 2%, the maximum acceptable concentration of this GRAS compound based on CFR 21, 184.1666. Therefore, these hams met the legal requirements for commerce and were safe for human consumption and can be used to mitigate and help control mite infestations and mold growth of hams that are aged longer than 5 months. Highlights: Nets treated with food-grade coatings controlled mold on hams in aging facilities. Nets reduced mold and mite growth in a mite-infested aging room. Treatment hams had negligible propylene glycol and were safe for human consumption.